ANALISIS PENGARUH LITERASI KEUANGAN, INKLUSI KEUANGAN DAN LIFESTLYE TERHADAP PERILAKU FINANSIAL PADA IGENERATION (Z) - Ghegana Ariel Sheda (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2023)
The purpose of this study is to analyze the effect of financial literacy, financial inclusion and lifestyle on financial behavior in iGeneration Z in Surakarta City. In this study using a type of quantitative research from primary data management sources, with the technique of distributing questionnaires to 100 respondents. Data analysis using multiple linear regression analysis method. Based on the results of this study, several conclusions can be drawn, namely the variables Financial Literacy (X1), Financial Inclusion (X2), Lifestyle (X3) have a positive and significant effect on financial behavior in iGeneration Z in Surakarta City. Based on the results of this study, it is hoped that Generation Z can maintain their financial behavior and of course also increase financial literacy and pay attention to lifestyles that meet their needs not desires, so that their financial behavior will continue to improve.